If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 4 = 34 Reorder the terms: 4 + 3n = 34 Solving 4 + 3n = 34 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3n = 34 + -4 Combine like terms: 4 + -4 = 0 0 + 3n = 34 + -4 3n = 34 + -4 Combine like terms: 34 + -4 = 30 3n = 30 Divide each side by '3'. n = 10 Simplifying n = 10
| -2x+5+7x=55 | | 4(p+6)=8p | | x^3-6X^2-x+30=0 | | 11r-2=24 | | 100-2n=60 | | -11-2=24 | | 3x-2=4x+6 | | 4x+7=3x+8 | | 3x+x+10=180 | | -6x-4=-64 | | m=21 | | -3x(x-4)-2x(x+3)= | | 2+x=-10 | | -52-3a=8 | | x+2y=27 | | 2x-26=-38+23x | | 16t^2-8t-15=0 | | 4x+7-3x=11 | | x=-3+-1.5Y | | 2x^2+16x+23=0 | | 4t-(5+2t)=37 | | 3x+5y=24 | | 6w+2w=25+47 | | 5(4x+7)-3(5-2x)=98 | | 3x-15=3(x-5) | | x^4=144 | | x-6=-3+9 | | 10-8x=91-29x | | (3x+4)(5x+8)= | | 2x+8+4x-3= | | (4+6)(2+4x)=45-2.5(x+3) | | -6(5-2n)=-6 |